Taking the strain - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Low-cost load-carrying devices: the design and manufacture of some basic means of transport by Ron Dennis and Alan Smith 1995 180pp price UKL 14.95 ISBN 1 85339 265 0 (Pbk)